2010
DOI: 10.1097/mat.0b013e3181e5d543
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler Measurements Correlate With Central Venous Pressure in Pediatric Patients After Cardiac Surgery

Abstract: Tissue Doppler imaging (TDI) measurements have been demonstrated to correlate with central venous pressure (CVP) in adults. We hypothesize that TDI measurements also correlate with CVP in children after cardiac surgery. Patients younger than 10 years with invasive CVP monitoring after cardiac surgery were studied. Annular tissue and atrioventricular inflow velocities were measured daily during CVP monitoring. Tissue Doppler imaging measurements were compared with CVP by univariate analyses. Subgroup analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…Early assessment of RV dysfunction or elevated pulmonary pressure could greatly benefit the care for critically ill newborns. Other studies have already shown promising results indicating that TDI might deliver new opportunities for assessing right ventricular function . Although we were not able to completely attribute the decrease in RV free wall PSS to the development of BPD, we could show a change in RV free wall PSS in groups with BPD on day 14.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Early assessment of RV dysfunction or elevated pulmonary pressure could greatly benefit the care for critically ill newborns. Other studies have already shown promising results indicating that TDI might deliver new opportunities for assessing right ventricular function . Although we were not able to completely attribute the decrease in RV free wall PSS to the development of BPD, we could show a change in RV free wall PSS in groups with BPD on day 14.…”
Section: Discussioncontrasting
confidence: 67%
“…Other studies have already shown promising results indicating that TDI might deliver new opportunities for assessing right ventricular function. [39][40][41] Although we were not able to completely attribute the decrease in RV free wall PSS to the development of BPD, we could show a change in RV free wall PSS in groups with BPD on day 14. At this age, there was no difference in RV free wall PSS when examining the effect of MV.…”
Section: Discussionmentioning
confidence: 64%
“…Evaluating diastolic function in patients with single ventricle physiology noninvasively is usually subjective despite the fact that diastolic dysfunction may be associated morbidity and mortality in this complex patient population. [1][2][3][4]15,16 Previous studies have shown mixed results with correlating echocardiographic values with catheterization VEDP. [5][6][7][8]10 In this study, S/D ratio correlated significantly with catheter derived VEDP in patients with single RV physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have shown modest correlation between TDI values and end diastolic pressures measured invasively in patients with single ventricle physiology. 28,29 However, approximately 30% of respondents graded diastolic function qualitatively. One has to assume that if qualitative grading of systolic function was less than ideal, 27 qualitative diastolic grading would be beset with even more inconsistencies.…”
Section: Patterns Of Noninvasive Evaluation Of Hlhs E77mentioning
confidence: 99%
“…More data need to be obtained, but initial studies at least appear to indicate that TDI and deformation analysis hold promise as a measurement for diastolic function in this population. [28][29][30] TDI measurement was the method that respondents would follow most often longitudinally to assess for diastolic function. This may be due to the ease in obtaining these values, its reproducibility, and the data in adults supporting this measurement as valid.…”
Section: Patterns Of Noninvasive Evaluation Of Hlhs E77mentioning
confidence: 99%